1995
DOI: 10.1002/jcp.1041650215
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of transforming growth factor‐β growth regulatory effects and receptors on bovine mammary cells

Abstract: Transforming growth factor-beta (TGF-beta) has been shown to inhibit mammary morphogenesis, growth, and differentiation in murine studies. We have characterized TGF-beta receptors and their autoregulation, and the growth response to TGF-beta 1 and TGF-beta 2 in cultured bovine mammary epithelium (MAC-T) and fibroblasts. Affinity labelling studies revealed that fibroblast and epithelial cells contained type I, II, and III (betaglycan) receptors, with the type III receptor being the predominant binding component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…Others have also shown that the TGF␤ receptors are under autoregulation control by ligand stimulation (18). It has been previously shown that treatment with TGF␤1 leads to down-regulation of TGF␤RII levels (19).…”
Section: Discussionmentioning
confidence: 98%
“…Others have also shown that the TGF␤ receptors are under autoregulation control by ligand stimulation (18). It has been previously shown that treatment with TGF␤1 leads to down-regulation of TGF␤RII levels (19).…”
Section: Discussionmentioning
confidence: 98%
“…TGFb1 has been shown to inhibit bovine mammary epithelial cell proliferation (Woodward et al 1995, Purup et al 2000a.…”
Section: Discussionmentioning
confidence: 99%
“…4). We also measured TGFb1 expression because it is increased in the serum of rapidly growing heifers and has been shown to inhibit MAC-T and pMEC proliferation (Woodward et al 1995, Purup et al 2000a. TGFb1 expression was not affected by development or nutrition (Fig.…”
Section: Effects Of Development and Nutrition On Mfp Production Of Irmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of growth factors, such as TGF-P and PDGF-AB, to stimulate fibroblast proliferation and protein synthesis in vitro has been studied previously for ligament cells [9,30]. A significant difference between the two TGF-P isoforms (TGF-PI and TGF-P2) has not been demonstrated in adult cells [5,31]. As we had previously shown TGF-P2 to result in formation of a larger scar mass and increased type I collagen production with an in vivo MCL model [28], this isoform was selected for this continuing study of delivery method, dose-dependence, and interaction with…”
Section: Introductionmentioning
confidence: 99%